Relationship between Corporate Social Responsibility, Dividend Payout, EBITDA, and Earnings per Share: An Empirical Analysis of 40 Listed Companies in NSE: An Empirical Analysis of the Relationship between CSR, Dividend Payout, EBITDA, and EPS in Listed Companies in NSE (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Corporate Social Responsibility (CSR) has been extensively studied in the past to assesses the relationship between CSR of companies and (Earning per share) EPS and (Earnings before interest depreciation tax and amortization (EBIDTA). A case study of 40 large size companies in India that are listed in National Securities Exchange (NSE). The research uses secondary data for primary analysis and applies MS Excel to analyze data. The data was collected from annual company reports and NSE website for the past 5 years. The research used CSR spending and EPS and dividends to analyze the impact of CSR of companies and there earnings per share and dividends payable.It was found that the relationship between CSR and Dividend per share (DPS) is positive, which implies that higher the CSR higher will be DPS. It was also assessed that there is no significant relationship between CSR spending and earnings per share (EPS). Positive relationship is assessed between CSR and EBIDTA from 2013 to 2016. But is shows negative correlation in the year 2017.